PENGARUH PEMBERIAN REBUSAN KAYU MANIS TERHADAP PENURUNAN HIPERTENSI PADA IBU HAMIL TRIMESTER 3 DI PUSKESMAS KARANGAPWITANKABUPATEN GARUT TAHUN 2025 - Yunia, Sela; Jayatmi, Irma; Yolandia, Rita Ayu (SINERGI : Jurnal Riset Ilmiah, 2025)
Hypertension in pregnancy (HDK) is a medical problem that usually occurs during pregnancy and causes complications in 2-3% of pregnancies. The prevalence of hypertension in pregnant women in 2023 in Garut Regency was recorded at 12.8%. The short-term impacts of hypertension in pregnancy include the mother and fetus. In addition to drugs, therapy for pregnant women with hypertension can be given cinnamon decoction therapy. The high incidence of hypertension needs to be prevented because hypertension can cause death. The purpose of this study was to determine the effect of cinnamon decoction on reducing hypertension in pregnant women in the third trimester. This research method uses a quasi-experimental with a pretest posttest one group design. The population in this study were all pregnant women who underwent examinations and were diagnosed with hypertension as many as 36 people, the sample technique used total sampling with a sample size of 36 respondents. The instruments used were equipment to measure blood pressure and a set of tools to record the results. Data analysis used a one-group t-test. The results of the study showed that the average systolic blood pressure before being given chayote was 146.47 an.